A new species of lizard in the genus Caledoniscincus (Reptilia: Scincidae) from southern New Caledonia and a review of Caledoniscincus atropunctatus (Roux) - Sadlier, Ross A.; Bauer, Aaron M.; Wood, Perry Jr. L.; Smith, Sarah A.; Jackman, Todd R. (Zootaxa, 2013)
A new species of skink, Caledoniscincus notialis sp. nov., is described from the ultramafic ranges in southern New Caledonia. It is most similar to, and has previously been referred to Caledoniscincus atropunctatus (Roux), a species with a widespread distribution throughout the Grand Terre and Loyalty Islands. The new species is distinct genetically from all other Caledoniscincus and can be distinguished by a unique pattern of dorsal coloration in males. Its range extends over much of the extensive ultramafic block in the south of the island, including the Goro Plateau and the mountain ranges at the southern edge of the Chaine Centrale north to Mt. Humboldt. It occurs mainly in humid forest habitat, much of which is now present only as isolated fragments in southern New Caledonia. Its preference for a habitat that has undergone a significant reduction in area of extent in a region under pressure from a range of anthropogenic threats suggests this new species is of conservation concern, and could be ranked as Vulnerable under IUCN listing. The genetic relationships of a redefined Caledoniscincus atropunctatus identifies two major subgroups, one located mainly in the northern and central-east regions of Grand Terre and the other in the southern and central-west regions and also including the population on the Loyalty Islands.